2016
DOI: 10.1111/fwb.12759
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining survival of European eels in two unexploited sub‐populations

Abstract: 1. Estimating accurate age-specific survival probabilities and understanding the processes (density dependent or independent) that regulate this demographic parameter are fundamental to propose sustainable management options for the endangered European eel (Anguilla anguilla). 2. In the present study, we used extensive mark-recapture data sets (13 and 17 years) on eel >150 mm to estimate accurate natural survival probabilities of two eel sub-populations, from the Oir and Fr emur rivers, western France, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Restocking eels for conservation purpose could be a promising option for sustaining eel populations. However, this action warrants more investigation regarding the carrying capacity of the selected receiving area, since it could influence both yellow eel survival 21 59 and future sex ratio 21 23 . The combined use of the sex markers that we propose would be useful to readily assess the population sex-ratio in a specific river/lagoon, where transplantations take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restocking eels for conservation purpose could be a promising option for sustaining eel populations. However, this action warrants more investigation regarding the carrying capacity of the selected receiving area, since it could influence both yellow eel survival 21 59 and future sex ratio 21 23 . The combined use of the sex markers that we propose would be useful to readily assess the population sex-ratio in a specific river/lagoon, where transplantations take place.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is not yet a clear understanding of what will be the long-term consequences of massive juvenile eel transplantation on future adult sex ratios, considering that sex determination is density-dependent. In eels, the sex ratio happens to be site-specific, with rivers geographically close producing a majority of males or a majority of females 21 . Usually, a greater proportion of males being observed in the downstream part of the watershed (high density), while females prefer to inhabit the rivers upstream 22 .…”
mentioning
confidence: 99%
“…Polders are characterised by a network of canals, connected ponds and ditches, resulting in a high habitat diversity and thus many potential growth areas (Lasne, Acou, Vila‐Gispert, & Laffaille, ). This could lead to higher growth rates, and larger eels have a higher survival rate (Boulenger et al., ). In addition, these areas are located close to the sea and may therefore, in the absence of migration barriers, be easily colonised by glass eels (Laffaille, Baisez, Rigaud, & Feunteun, ).…”
Section: Introductionmentioning
confidence: 99%
“…and larger eels have a higher survival rate (Boulenger et al, 2016). In addition, these areas are located close to the sea and may therefore, in the absence of migration barriers, be easily colonised by glass eels (Laffaille, Baisez, Rigaud, & Feunteun, 2004).…”
mentioning
confidence: 99%
“…Recently, Podgorniak et al (2015) demonstrated that human-induced obstacles to migration could act as an evolutionary pressure. Concerning this, Boulenger et al (2016) highlighted that…”
Section: Assessing the Impact Of Anthropogenic Pressures At The Distrmentioning
confidence: 99%